Serum lipid profiles and glycemic control in adolescents and young adults with type 1 diabetes mellitus - Shin-Hee Kim; In-Ah Jung; Yeon Jin Jeon; Won Kyoung Cho; Kyoung Soon Cho; So Hyun Park; Min Ho Jung; Byoung Kyu Suh (Korean Society of Pediatric Endocrinology, 2014)
PurposeWe aimed to investigate serum lipid profiles and glycemic control in adolescents and young adults with type 1diabetes mellitus (T1DM).MethodsThis cross-sectional study included 29 Korean young adults and adolescents with T1DM. The median age was 17 years (range, 10-25 years) and 18 (62.1%) were female. We compared the lipid profiles of patients with dyslipidemia and those without dyslipidemia. Correlations between glycosylated hemoglobin (HbA1c) and lipid profiles (total cholesterol [TC], low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C], and triglyceride [TG]) were determined by linear regression analysis.ResultsOf the 29 patients with T1DM, 11 (37.9%) were classified as having dyslipidemia due to the following lipid abnormality: TC≥200 mg/dL in 8 patients, LDL-C≥130 mg/dL in 4 patients, TG≥150 mg/dL in 2 patients, and HDL-C≤35 mg/dL in 2 patients. Compared to patients without dyslipidemia, patients with dyslipidemia were more likely to have higher values of HbA1c (median, 10.6%; range, 7.5%-12.3% vs. median, 8.0%; range, 6.6%-10.0%; P=0.002) and a higher body mass index z score (median, 0.7; range, -0.57 to 2.6 vs. median, -0.4; range, -2.5 to 2.2; P=0.02). HbA1c levels were positively correlated with TC (P=0.03, R2=0.156) and TG (P=0.005, R2=0.261).ConclusionA substantial proportion of adolescents and young adults with T1DM had dyslipidemia. We found a correlation between poor glycemic control and poor lipid profiles in those patients.